Kerosene biodegradation in the grasses’ rizosphere under greenhouse conditions - García, Elizabeth (2013)
Kerosene affects in a negative way the soil biological activity, also the growth and development of the plant. To examine the aforesaid, this contaminant was evaluated in oats plants (Avena sativa), barley (Hordeum vulgare), grass (Chloris gayana) and wheat (Triticum aestivum), in the microbial populations of the rizosphere and rhizoplane. Also determined was the contaminant’s degradation percentage in the rizospheric soil of the different grasses. A completely at random experimental design with a 2x4 factorial arrangement, was used, with 8 treatments and 5 repetitions each. The factors were kerosene doses (0 and 2000 mg.kg -1) and plant species. At 56 days after establishment of the experiment, the contaminated soil reduced significantly (p≤0.05), the foliar area, the total dry matter and the root volume of the 4 grasses, compared to those established in soil without contamination. In the contaminated soil the total microbial populations in the rhizoplane and the plant rizosphere increased; while those that used the hydrocarbon as carbon source increased in the rhizoplane. The mycorrhizal colonization went from 28.8 to 15.7%, and when the soil was contaminated it was reduced from 11.4 to 5%; however, the endomycorrizal fungus performed its functions even with the hydrocarbon present in the soil. The oats rizosphere allowed a kerosene degradation of 84.4%, while that of the grass only 39.6%. It is convenient to expand the rizospheric studies with another organic contaminant, to determine the oats’ rizospheric effectiveness and to evaluate if the hydrocarbon is accumulated in its tissues.